A Novel Porcine Model for the Study of Cerebrospinal Fluid Dynamics: Development and Preliminary Results - Fleischman, David; Kaskar, Omkar; Shams, Rayad; Zhang, Xinxin; Olson, Daniel; Zdanski, Carlton; Thorp, Brian D.; Kuznetsov, Andrey V.; Grace, Landon; Lee, Yueh Z. (Frontiers in Neurology, 2019)
Idiopathic intracranial hypertension, space-flight associated neuro-ocular syndrome (SANS), and glaucoma are conditions that are among a spectrum of cerebrospinal fluid (CSF)-related ophthalmologic disease. This implies that local CSF pressures at the level of the optic nerve are involved to variable extent in these disease processes. However, CSF pressure measurements are problematic due to invasiveness and interpretation. The pressure measured by a lumbar puncture is likely not the same as the orbital CSF pressure. It is believed this is at least in part due to the flow restrictive properties of the optic canal. A model for CSF dynamics was created using three medium-sized pigs. Contrast was administered through a lumbar subarachnoid space access. The contrast front was imaged with repeated computed tomographic (CT) imaging. Once contrast entered the orbit, rapid, sequential CT imaging was performed until the contrast reached the posterior globe. Head tilting was performed accentuating to highlight the role of gravitational dependence within the subarachnoid space.